RIPAP Application Design for Early Detection of Disease Risk Due to Diving Based on WEB - Rachmawati, Dhian Satya; Amalin, Atika Mima; Chabibah, Nur (Journal of Health Science and Prevention, 2025)
Most Indonesians living in coastal areas worked as fishermen or traditional divers. They needed to understand the signs and symptoms of barotrauma or decompression to provide first aid. Early detection of diving-related diseases was essential to improve their health status. This study aimed to design a web-based RIPAP application for the early identification of diving-related diseases to enhance the health status of fishermen. The study employed the prototype method in designing the web-based RIPAP application. The initial stages of system design included communication, rapid planning and modeling, quick design, prototype construction, development, delivery, and feedback. Testing was conducted using the black box method by health workers at the Kenjeran Community Health Center. The test results indicated that the system functioned well in each process flow. Of the seven processes carried out by three users, all were successfully executed by the system. The feasibility test results from users for functional aspects and benefits showed that the application’s feasibility level was "Decent" at a rate of 66.7%. The benefits aspect, with a 100% rate, indicated that the application was "Highly Valuable." These results suggested that the application was sufficiently good for future implementation. The testing also confirmed that the RIPAP application was able to perform all processes as desired by the users and was categorized as "Feasible" for implementation by health workers.